THE EFFECTIVENESS OF MODERN SUPERPLASTICIZERS IN LOW-DURABLE CONCRETES - Netesa, M. I. (Science and Transport Progress, 2005)
The article deals with the issue of using super-plasticizers in concrete grades with strength less than 20 MPa, which provides substantial economic effect.